IDENTIFIKASI KESULITAN BELAJAR MAHASISWA PADA MATA KULIAH KUANTITI SURVEYING PROGRAM STUDI PENDIDIKAN TEKNIK BANGUNAN FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - 809-818 , Sulistyono (Universitas Negeri Padang, 2015)
ABSTRACT Based of motivated by the problems there are still many students of Technical Education Building that received low grades in courses Quantity Surveying. The purpose of this study is to determine what are the difficulties faced by students while attending lectures. This research is descriptive with quantitative approach . Subjects in this study were students who had finished the course in Quantity Surveying half of July to December 2014 by 99 students . The sampling technique using purposive sampling with a sample of 32 students. Data collection techniques using a questionnaire, which is spread by the researcher and filled by the students. Data analysis technique used is descriptive analysis technique with percentage. The results showed that the indicator of the ability to remember the students in the category simply by percentage of 67.58 % , while the indicator of the ability to understand into the low category with a percentage of 61.17 % , an indicator of ability to implement in a lower category by percentage of 63.19 % , while the ability to analyze low in the category with the percentage of 61.56 % . The overall ability of students is still low. Key words : Kesulitan Belajar , Mahasiswa , Kuantiti Surveying